서울시 오피스텔 매매, 월세시장에 대한 연구 - 전해정(Hae-Jung Chun) (한국콘텐츠학회 논문지, 24(5), 2024)
최근 저출산, 고령화 등 인구구조의 변화로 인해 1-2인 가구가 증가하면서 오피스텔에 대한 수요가 크게 늘어난 상황이다. 이에 본 연구는 서울시 오피스텔 매매, 월세시장을 예측하고자 내생변수는 서울시 5대 권역의 매매가격과 월세가격으로 정하고 외생변수는 산업생산지수, 회사채수익률, 주택건설인허가실적, 취업자수로 설정하여 2018년 1월부터 2023년 12월까지의 자료로 패널연립방정식을 구성해 연구하였다. 패널연립방정식의 분석결과를 보면, 오피스텔 월세가격이 1% 상승할 경우 오피스텔 매매가격은 1.504% 상승하였고 오피스텔 매매가격이 1% 상승할 경우 오피스텔 월세가격이 1.735% 상승하였다, 회사채수익률이 1%p 상승하면 오피스텔 매매가격은 0.006% 하락하는 것으로 나타났고 취업자수 1% 증가는 오피스텔 월세가격이 0.117% 상승하는 것으로 나타났다. 지역별 모형에 대한 예측력을 분석한 결과, 권역별 MAPE, MSE, MAE 수치를 종합해 보면, 동남권 모형의 적합도와 예측력이 가장 높고, 서남권이 가장 낮은 것으로 나타났다. Recently, the demand for officetels has increased significantly as the number of one- or two-person households has increased due to changes in population structure such as low birth rate and aging. In order to predict the officetel market in Seoul, this study set the endogenous variables as sale prices and monthly rent prices in the five major districts of Seoul, and set the exogenous variables as the industrial production index, corporate bond yield, housing construction license performance, and number of employed people from January 2018 to 2023. A panel system of equations was constructed and studied using data up to December 2018. Looking at the results of the panel equations, when the officetel monthly rent rises by 1%, the officetel sale price rises by 1.504%, and when the officetel sale price rises by 1%, the monthly rent price rises by 1.735%. When the corporate bond yield rises by 1%p, the officetel sale price rises by 1.504%. The officetel sales price was found to decrease by 0.006%, and a 1% increase in the number of employed people resulted in a 0.117% increase in the officetel monthly rent. As a result of analyzing the predictive power of the model by region, when combining the MAPE, MSE, and MAE values for each region, it was found that the model in the southeastern region had the highest fit and predictive power, and the southwest region had the lowest. KCI Citation Count: 0